2022
DOI: 10.1096/fj.202101789rr
|View full text |Cite
|
Sign up to set email alerts
|

High‐fat, sucrose and salt‐rich diet during rat spermatogenesis lead to the development of chronic kidney disease in the female offspring of the F2 generation

Abstract: Effects of feeding male rats during spermatogenesis a high‐fat, high‐sucrose and high‐salt diet (HFSSD) over two generations (F0 and F1) on renal outcomes are unknown. Male F0 and F1 rats were fed either control diet (F0CD+F1CD) or HFSSD (F0HD+F1HD). The outcomes were glomerular filtration rate and urinary albumin excretion in F1 and F2 offspring. If both outcomes were altered a morphological and molecular assessment was done. F2 offspring of both sexes had a decreased GFR. However, increased urinary albumin e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…A novel mechanism, initially proposed by Hocher et al (2000) and subsequently validated by other researchers ( Masuda et al, 2002 ; van Beynum et al, 2006 ; Tsai et al, 2008 ; Miodovnik et al, 2012 ; Warrington et al, 2019 ), suggests that maternal genes may influence the fetal phenotype independently of the fetal genome. Similarly, existing studies have already suggested that paternal genes, even without being transmitted to the offspring, may also influence the phenotype of the offspring ( Nelson et al, 2010 ; Chen et al, 2012 ; Li et al, 2016 ; Zhang et al, 2019 ; Liu et al, 2021 ; Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 92%
“…A novel mechanism, initially proposed by Hocher et al (2000) and subsequently validated by other researchers ( Masuda et al, 2002 ; van Beynum et al, 2006 ; Tsai et al, 2008 ; Miodovnik et al, 2012 ; Warrington et al, 2019 ), suggests that maternal genes may influence the fetal phenotype independently of the fetal genome. Similarly, existing studies have already suggested that paternal genes, even without being transmitted to the offspring, may also influence the phenotype of the offspring ( Nelson et al, 2010 ; Chen et al, 2012 ; Li et al, 2016 ; Zhang et al, 2019 ; Liu et al, 2021 ; Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 92%
“…44 Moreover, paternal HFD-induced obesity is associated with renal triglyceride accumulation and histological changes in tubules, accompanied by upregulated expression of acetyl-CoA acetyltransferase 1, and epigenetic alterations of renal mRNA expression of genes (Enpp6, Tmem144, Cd300lf, and Actr3b) in offspring, implying a higher risk of chronic kidney disease. 45,46 High sugar intake…”
Section: High-fat Intakementioning
confidence: 99%
“…Further investigation on the brain has demonstrated that male exposure to the HFD may contribute to stable behavioral variation among females in courtship, maternal care, and anxiety‐like behavior, 43 as well as cognitive impairments in the offspring due to altered methylation and expression of the BDNF gene 44 . Moreover, paternal HFD‐induced obesity is associated with renal triglyceride accumulation and histological changes in tubules, accompanied by upregulated expression of acetyl‐CoA acetyltransferase 1, and epigenetic alterations of renal mRNA expression of genes ( Enpp6 , Tmem144 , Cd300lf , and Actr3b ) in offspring, implying a higher risk of chronic kidney disease 45,46 …”
Section: Effects Of Paternal Diet and Nutrition On Offspringmentioning
confidence: 99%
“…In some studies, a maternal high-fat diet was applied as the first hit, followed by a second hit to induce kidney disease in later life. For instance, animal models of a maternal and postnatal high-fat diet [ 82 ] and a combined maternal high-fat, high-sucrose, and high-salt diet [ 83 ] have been used to study renal programming. Another hit may trigger the same programming mechanisms and amplify adverse actions culminating in a disease state.…”
Section: Renal Programming: the Impact Of A Maternal High-fat Dietmentioning
confidence: 99%